2022
DOI: 10.3390/w14030337
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Trends in High and Low River Flows in Upper Indus Basin, Pakistan

Abstract: The Upper Indus Basin (UIB) features the high mountain ranges of the Hindukush, Karakoram and Himalaya (HKH). The snow and glacier meltwater contribution feeds 10 major river basins downstream including Astore, Gilgit, Hunza, Jhelum, Kabul, Shyok and Shigar. Climate change is likely to fluctuate the runoff generated from such river basins concerning high and low streamflows. Widening the lens of focus, the present study examines the magnitude and timing of high flows variability as well as trends variability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…At the majority of the locations, there were significant increasing trends from June to August, which were endorsed by the previous studies [54,72]. Hydrological drought timeseries from October to March showed substantial lowering trends on a monthly scale, which is similar to the findings of earlier research that found clear patterns towards increasing streamflow from October to March [54,73]. However, hydrological drought timeseries from April to September exhibited significant increasing trends, and these results were also found to be consistent with preceding research [54,72,75].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…At the majority of the locations, there were significant increasing trends from June to August, which were endorsed by the previous studies [54,72]. Hydrological drought timeseries from October to March showed substantial lowering trends on a monthly scale, which is similar to the findings of earlier research that found clear patterns towards increasing streamflow from October to March [54,73]. However, hydrological drought timeseries from April to September exhibited significant increasing trends, and these results were also found to be consistent with preceding research [54,72,75].…”
Section: Discussionsupporting
confidence: 87%
“…Three (03) stations, i.e., Gilgit, Besham Qila, Kalam, and Chitral, detected significant decreasing trends in January, whereas Jhansi Post and Thal stations detected significant increasing trends. At Besham Qila, where the Indus River is flowing (upstream of Tarbela), it was found to be increasing at a rate of 6%, according to research [73]. The Besham flows from 1969 to 1995 were also examined by Ashraf et al [72], who discovered an escalating trend.…”
Section: Discussionmentioning
confidence: 96%